Perbandingan Metode Continuous Review dan Periodic Review Dalam Pengendalian Persediaan Bahan Baku (studi kasus: UD. Keripik Cinta Mas Hendro) - Rahayu, Aida; Manurung, Asima (Leibniz: Jurnal Matematika, 2024)
UD. Keripik Cinta Mas Hendro is a business that produces snacks, the most popular product is cassava chips, with poor policies it is very risky for consumer demand and costs incurred in cassava inventory. This study aims to optimize the total inventory cost and obtain the right method in inventory control using Continuous Review and Periodic Review. The calculation results show that Continuous Review is the right method with a minimum cost of Rp 3,305,310,721 with a savings percentage of 4.70% and has an order size of q = 230,121.99 kg, and a reorder point r = 9,967.13 kg.